Ro52 autoantibodies arise from self-reactive progenitors in a mother of a child with neonatal lupus. (May 2017) - Reed, Joanne H.; Gorny, Miroslaw K.; Li, Liuzhe; Cardozo, Timothy; Buyon, Jill P.; Clancy, Robert M.
Abstract: The detection of cardiac conduction defects in an 18–24 week old foetus in the absence of structural abnormalities predicts with near certainty the presence of autoantibodies against 60kD and 52kD SSA/Ro in the mother regardless of her health status. Previous studies have emphasized these autoantibodies as key mediators of tissue injury. The aim of this study was to focus on the anti-Ro52 response to determine whether these autoantibodies originate from progenitors that are inherently self-reactive or from B-cells that acquire self-reactivity during an immune response. We traced the evolution of two anti-Ro52 autoantibodies isolated from circulating IgG1-switched B-cells from an asymptomatic mother of a child with third degree congenital heart block. The autoantibodies were expressed as their immune form and as pre-immune ancestors by reverting somatic mutations to germline sequence. The reactivity of pre-immune and immune antibodies for Ro52, Ro60, La and DNA was measured. Both anti-Ro52 autoantibodies exhibited a low frequency of somatic mutations (3–4%) and utilised the same heavy and light chain genes but represented distinct clones based on differing complementarity determining region sequences. Pre- and post-immune antibodies showed specific binding to Ro52 with no measurable reactivity for other autoantigens. Ro52 binding was higher for immune antibodies compared to pre-immune counterparts demonstrating that autoreactivity was enhanced by affinity maturation. These data indicate that Ro52 reactivity is an intrinsic property of the germline antibody repertoire in a mother with a pathogenic antibody defined by cardiac injury in her offspring, and implies defects in both central and peripheral tolerance mechanisms. Highlights: Ro52 B cells were isolated from a mother of 2 children with autoimmune heart block. Ro52 autoantibodies derive from self-reactive naïve B cells. Ro52 autoantibodies undergo affinity maturation to enhance Ro52 binding.